Guinea : 2007 Article IV Consultation and Staff Report for the 2007 Article IV Consultation and Requests for Three-Year Arrangement Under the Poverty Reduction and Growth Facility and for Additional Interim Assistance Under the Enhanced Heavily Indebted Poor Countries Initiative; Staff Report; Staff Supplement; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Guinea. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Guinea has implemented an impressive policy shift toward macroeconomic stabilization under the economic program. Executive Directors commended this development and stressed the need for tight fiscal and monetary policies and welcomed the debt sustainability analysis and implementation of the Extractive Industries Transparency Initiative. They emphasized the need for reinstating fiscal control, improving governance, implementing structural reforms, sustained assistance from the international community to boost economic growth, and encouraged the authorities to take necessary steps to reach the HIPC completion point and qualify for debt relief under these initiatives.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet